Socio-Economic Analysis of Tourism: Evidence from Calabar Metropolis, Cross River State, Nigeria - Obong, Linus Beba; Etim, Offiong Effiong (Journal of Tourism Management Research, 2019)
The paper was focused on the socio-economic analysis of tourism impacts on the economy with evidence from Calabar Metropolis, Cross River State, Nigeria. Data for the study was generated from well-structured questionnaire administration. The generated data was analyzed using descriptive statistic; while three hypothesis were tested in the study using and results shows that there is a significant difference between the socio-economic impact of tourism and the internally generated revenue; there is a significant difference between the impact of tourism on households and private businesses within the Metropolis; and there is no significant variation in the challenges faced by private businesses associated with tourism in the study area. Based on the findings, it was recommended that tourism experts should be employed to pilot the affairs of tourism to position the industry for greater benefits in the study area.